Proceedings of the 45th ACM Technical Symposium on Computer Science Education 2014
DOI: 10.1145/2538862.2538940
|View full text |Cite
|
Sign up to set email alerts
|

Integrating computational and creative thinking to improve learning and performance in CS1

Abstract: Our research is based on an innovative approach that integrates computational thinking and creative thinking in CS1 to improve student learning performance. Referencing Epstein's Generativity Theory, we designed and deployed a suite of creative thinking exercises with linkages to concepts in computer science and computational thinking, with the premise that students can leverage their creative thinking skills to "unlock" their understanding of computational thinking. In this paper, we focus on our study on dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 13 publications
4
23
0
Order By: Relevance
“…Like [4], there were several motivating factors in developing assignments with elements of creativity: provide an opportunity for students to take ownership and pride in their work and to support learning. Another approach described in [8] is to use creative thinking exercises to encourage students to learn about computation; these exercises were not part of the programming itself but focused more on novelty, challenging existing patterns, broadening knowledge and using new environments for stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Like [4], there were several motivating factors in developing assignments with elements of creativity: provide an opportunity for students to take ownership and pride in their work and to support learning. Another approach described in [8] is to use creative thinking exercises to encourage students to learn about computation; these exercises were not part of the programming itself but focused more on novelty, challenging existing patterns, broadening knowledge and using new environments for stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent follow-up studies examined differences between CS majors and non-CS majors, freshmen and upper class students, and men and women students [7]. Results showed that for the knowledge test, the linear "dosage effect" of increasing knowledge test scores with student completion of each additional exercise was consistent across all comparisons.…”
Section: Prior Studiesmentioning
confidence: 90%
“…As reported in [6,7,11,12], for all our CCEs, students work in groups to engage in a combination of hands-on problem solving, written analysis, and reflection. The collaborative nature of the CCEs facilitates creative thinking by bringing together students from diverse backgrounds.…”
Section: Overall Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study took place as part of a larger NSF-funded study geared towards improving students' abilities to learn computational thinking by incorporating computational and creative thinking exercises into undergraduate CS courses [14]. Participants completed the beginning of the semester Implicit Theories of Intelligence Scale, future time perspective measures, and additional assessments not used in this study during lab or lecture sessions during the first week of the semester.…”
Section: Methodsmentioning
confidence: 99%